Sweets and other sugary foods – a scoping review for Nordic Nutrition Recommendations 2023 - Henna Vepsäläinen; Emily Sonestedt (Food & Nutrition Research)
Background: Sweets, chocolate, and sweet bakery products are generally high in energy and added sugar, whereas the levels of essential nutrients and fibre are low. According to sales statistics, the consumption of sweets and chocolate is high in the Nordic and Baltic countries. Objective: This scoping review describes the totality of evidence for the role of sweets and other sugary foods for health-related outcomes as a basis for setting and updating food-based dietary guidelines in the Nordic Nutrition Recommendations 2023 (NNR2023) project. Design: We conducted a literature search to identify systematic reviews published between 2011 and 2021. The literature search resulted in 756 papers, of which 12 were included in this scoping review as sources of evidence. We also used evidence from the European Food Safety Authority’s (EFSA) scientific opinion on tolerable upper intake level for dietary sugars published in 2022. Results: Most of the papers included from the search focused on chocolate or cocoa, which are rich in flavonoids. We found some evidence linking chocolate consumption with lower blood pressure, lower risk of type 2 diabetes, and improved insulin markers, but the evidence was ranked low or very low. The search did not identify systematic reviews investigating the associations between other sugary food consumption and health outcomes. In the EFSA review, conclusions were not drawn for other sugar sources than sugar-sweetened beverages. However, for fasting glucose, total cholesterol, high-density lipoprotein (HDL) cholesterol, fasting triglycerides, and uric acid, there was a statistically significant effect of high sugar intake from solid foods compared to low sugar intake. Conclusion: Because sweets, chocolate, and other sugary foods are high in energy and added sugar, and low in essential nutrients and fibre, it is reasonable to limit their consumption, which is reported high in the Nordic countries.